Pengaruh Penguasaan Tekhnologi Informasi Dan Motivasi Kerja Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening (Studi pada Sekretariat Daerah Kota Semarang) - Novianty, Yurike; Indarto, Indarto; Budiati, Yuli (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research focuses on the Regional Secretariat of Semarang City and uses an Explanatory Research approach. The data of this research are: primary and secondary data. The population studied consisted of 210 employees of the Regional Secretariat of Semarang City, which were selected using stratified proportional random sampling technique. Data were collected through questionnaires, while the data were analyzed using PLS method. The research results, namely: mastery of information technology and work motivation significantly have a positive effect on job satisfaction. In addition, job satisfaction also has a positive and significant influence on employee performance. Mastery of information technology, work motivation also have a positive and significant effect on employee performance directly. Job satisfaction acts as an intervening variable in the relationship between mastery of information technology and work motivation with employee performance.